2021
DOI: 10.1007/s00432-021-03672-w
|View full text |Cite
|
Sign up to set email alerts
|

Survival predictors of 177Lu-Dotatate peptide receptor radionuclide therapy (PRRT) in patients with progressive well-differentiated neuroendocrine tumors (NETS)

Abstract: Purpose 177Lu-Dotatate is an emerging treatment modality for patients with unresectable or metastatic well-differentiated NETs. This study examines survival predictors in patients who received 177Lu-Dotatate. Methods A retrospective single-center review was conducted, examining 47 individuals with progressive well-differentiated NETs treated with 177Lu-Dotatate (four induction cycles of 5.5 GBq at 10-week intervals followed by eight maintenance cycles of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…A study by Papantoniou et al. ( 34 ) demonstrated that changes in chromogranin A and 5-hydroxyindoleacetic acid during treatment were not predictors of PRRT response ( 34 ), although baseline values correlated to PFS ( 34 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Papantoniou et al. ( 34 ) demonstrated that changes in chromogranin A and 5-hydroxyindoleacetic acid during treatment were not predictors of PRRT response ( 34 ), although baseline values correlated to PFS ( 34 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many clinical parameters have been proposed as prognostic markers. Factors associated with a reduction in PFS and OS in PRRT-treated patients were ascites ( 35 ), marked liver metastasis burden ( 18 , 25 , 35 ), unusual metastatic sites ( 35 ), and age >65 years at the time of PRRT ( 18 ). Other factors such as interim ascites, the presence of ≥5 bone metastases, and NETs other than GEP were predictors of worse OS ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various biological markers predictive for outcomes of PRRT have been studied. An elevated baseline level of CgA is associated with both decreased post-PRRT PFS [ 114 , 184 , 189 , 190 ] and OS [ 114 , 184 , 190 , 191 , 192 ]. A biochemical response in CgA levels is significantly associated with longer post-PRRT survival [ 184 , 193 ], while increases in CgA levels after PRRT correlates with worse OS [ 191 ].…”
Section: Predictive Factors For Response To Prrt In Advanced Pannensmentioning
confidence: 99%
“…Patients with bone metastases [ 59 , 183 , 184 , 187 , 188 , 190 , 198 , 214 ] as well as with higher hepatic tumor load [ 59 , 62 , 183 , 184 , 186 , 190 , 213 ] are reported to have a worse clinical outcome of PRRT. In addition to the findings that poor performance status, as well as previous treatment correlate with worse outcomes, as mentioned above, early initiation of PRRT can maximize its anti-tumor activity [ 282 ], which needs to be validated by prospective, randomized studies with other therapeutic agents.…”
Section: Predictive Factors For Response To Prrt In Advanced Pannensmentioning
confidence: 99%